Plasmodium vivax: parasitemia determination by real-time quantitative PCR in Aotus monkeys (2002)
Plasmodium vivax and Plasmodium falciparum are the two prevalent human malaria species. A Colombian P. vivax wild strain has been adapted in Aotus nancymaae monkeys for use in further biological and immunological studies. We present data validating a real-time PCR assay quantifying P. vivax parasitemia, using the small subunit ribosomal RNA genes as an amplification target. P. vivax species-specific primers were designed on the 18S ribosomal gene V8 region, for amplifying both asexual and sporozoite ssrRNA genes. The assay detects amplification products bound to fluorescent SYBR-Green I dye using Perkin–Elmer GeneAmp-5700-SDS. Linear range standard curves from 6 DNA concentration logs (+0.99 correlation coefficients) were obtained. Standard curves were constructed using a plasmid containing target gene for real-time PCR amplification. This P. vivax specific assay is very sensitive, having a three parasite detection limit, and is reproducible and accurate. It involves a “closed-tube” PCR, avoids time-consuming post-PCR manipulation, and decreases potential PCR contamination.